A educação ambiental nos projetos político-pedagógicos das escolas municipais de ensino fundamental da cidade de Araraquara/SP - Ferrari, Alexandre Harlei [UNESP]; Zancul, Maria Cristina de Senzi [UNESP] (My University, 2010)
In this paper, we aim at describing and assessing Environmental Education in Pedagogical Policy Projects (PPP) drawn by eight elementary schools belonging to the city school network of the city of Araraquara, in the State of São Paulo, Brazil. A framework was designed to detail references to topics and activities related to the environment contained in the respective PPP. Next, the information obtained was recorded under two categories: a) content and activities, and b) theoretical background. It was found that, although seven out of the eight PPP studied pointed to work towards environment-related topics, they do not enable the theoretical and methodological grounds behind their programmed actions be identified.

Nesse artigo descrevemos e analisamos as propostas de Educação Ambiental contidas nos Projetos Político-Pedagógicos (PPP) de oito escolas de Ensino Fundamental da rede municipal de Araraquara, Estado de São Paulo. Com a finalidade de detalhar as referências sobre os temas e as atividades relacionadas a Meio Ambiente contidas nos PPP, foi elaborado um roteiro e as informações obtidas foram separadas em duas categorias: a) conteúdos e atividades; b) fundamentos teóricos. Observou-se que, embora sete dos PPP apontem trabalhos com a temática ambiental, eles não trazem indicações que permitam identificar fundamentos teóricos e metodológicos para as ações programadas.
Keywords: Environmental Education; Elementary School; Pedagogical Policy Project; Educação Ambiental; Ensino Fundamental; Projeto Político-Pedagógico